Biology of upper-body and lower-body adipose tissue-link to whole-body phenotypes. - Karpe, F; Pinnick, K (Nature Publishing Group, 2015)
The distribution of adipose tissue in the body has wide-ranging and reproducible associations with health and disease. Accumulation of adipose tissue in the upper body (abdominal obesity) is associated with the development of cardiovascular disease, insulin resistance, type 2 diabetes mellitus and even all-cause mortality. Conversely, accumulation of fat in the lower body (gluteofemoral obesity) shows opposite associations with cardiovascular disease and type 2 diabetes mellitus when adjusted for overall fat mass. The abdominal depots are characterized by rapid uptake of predominantly diet-derived fat and a high lipid turnover that is easily stimulated by adrenergic receptor activation. The lower-body fat stores have a reduced lipid turnover with a capacity to accommodate fat undergoing redistribution. Lower-body adipose tissue also seems to retain the capacity to recruit additional adipocytes as a result of weight gain and demonstrates fewer signs of inflammatory insult. New data suggest that the profound functional differences between the upper-body and lower-body tissues are controlled by site-specific sets of developmental genes, such as HOXA6, HOXA5, HOXA3, IRX2 and TBX5 in subcutaneous abdominal adipose tissue and HOTAIR, SHOX2 and HOXC11 in gluteofemoral adipose tissue, which are under epigenetic control. This Review discusses the developmental and functional differences between upper-body and lower-body fat depots and provides mechanistic insight into the disease-protective effects of lower-body fat.